Dylematy związane z parytetem siły nabywczej - Ignaszewska, Katarzyna (The Dilemmas of Applying the Purchasing Power Parity, 2006)
The purchasing power parity is an artificial currency that reflects differences in national price level that are not taken into account economic indexes (for example GDP) by exchange rate. This unit allows meaningful volume comparisons of economic indicators over countries. The author presents in this paper "for and against" of using the purchasing power parity in exchange for exchange rate.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 180-186